Elucidation of the structure of retroviral proteases: a reminiscence. (28th August 2015) - Jaskolski, Mariusz; Miller, Maria; Mohana Rao, J. K.; Gustchina, Alla; Wlodawer, Alexander
Abstract : Determinations of only a very few protein structures had consequences comparable to the impact exerted by the structure of the protease encoded by HIV‐1, published just over 25 years ago. The structure of this relatively small protein and its cousins from other retroviruses provided a clear target for a spectacularly successful structure‐assisted drug design effort that offered new hope for controlling the then‐escalating AIDS epidemic. This reminiscence is limited primarily to work conducted at the National Cancer Institute, and is not meant to be a comprehensive history of the field, but is rather an attempt to provide a very personal account of how the structures of this most thoroughly studied crystallographic target were determined. Abstract : The structure of the HIV‐1 protease and its relatives from other retroviruses were first reported just over 25 years ago. The HIV‐1 protease structure provided a clear target for a spectacularly successful structure‐assisted drug design effort that offered new hope for controlling the then‐escalating AIDS epidemic. In the first of our new 'Discovery‐in‐Context Reviews', Features Editor and Editorial Board member Alexander Wlodawer and his colleagues provide a personal account of their research − conducted in the then newly established Crystallography Laboratory at the Frederick (Maryland) campus of the National Cancer Institute − to determine the structures of this important crystallographic target.